Agrobacterium-mediated vacuum infiltration and floral dip transformation of rapid-cycling Brassica rapa - Die Hu; Andrew F. Bent; Xilin Hou; Ying Li (BMC Plant Biology, 2019)
Abstract Background Rapid-cycling Brassica rapa (RCBr), also known as Wisconsin Fast Plants, are small robust plants with a short lifecycle that are widely used in biology teaching. RCBr have been used for decades but there are no published reports of RCBr genetic transformation. Agrobacterium-mediated vacuum infiltration has been used to transform pakchoi (Brassica rapa ssp. chinensis) and may be suitable for RCBr transformation. The floral dip transformation method, an improved version of vacuum infiltration, could make the procedure easier. Results Based on previous findings from Arabidopsis and pakchoi, plants of three different ages were inoculated with Agrobacterium. Kanamycin selection was suboptimal with RCBr; a GFP screen was used to identify candidate transformants. RCBr floral bud dissection showed that only buds with a diameter less than 1 mm carried unsealed carpels, a key point of successful floral dip transformation. Plants across a wide range of inflorescence maturities but containing these immature buds were successfully transformed, at an overall rate of 0.1% (one per 1000 T1 seeds). Transformation was successful using either vacuum infiltration or the floral dip method, as confirmed by PCR and Southern blot. Conclusion A genetic transformation system for RCBr was established in this study. This will promote development of new biology teaching tools as well as basic biology research on Brassica rapa.